Representation of politeness in tabe' speech of the people of Idampang village, Gantarang Keke sub-district, Bantaeng district: Representasi kesantunan tutur kata tabe' masyarakat desa idampang, kecamatan gantarang keke, kabupaten bantaeng - Kaharuddin; Sitti Hajar; Ridha Ichwanty Sabir; Andi Marwan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Tabe” iis ian iexample iof iancestral icultural iheritage ior ilocal iwisdom iof ithe ipeople iof iSouth iSulawesi ito irespect ior irespect iother ipeople. i